CREATINE SUPPLEMENTATION IN INFLAMMATORY BOWEL DISEASE: LITERATURE REVIEW - Bułat, Aleksandra; Sydor, Mateusz; Plizga, Wojciech; Lepa, Zuzanna (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Inflammatory bowel disease (IBD) consists of two leading types of relapsing and remitting diseases that are increasing in incidence and prevalence. The highest prevalence of ulcerative colitis (UC) and Crohn’s disease (CD) has been reported in North America, the UK, and northern Europe. The incidence of IBD ranges from 5/100000/year(CD) to 9-20cases per 100000person-years, with 15–20% of patients diagnosed in childhood. Therapy usually consists of immunosuppressive medications and biologics, which carry multiple side effects. Despite it, surgery may be required to achieve remission. Creatine supplementation has been linked to improving gastrointestinal (GI) health and has potential in reducing or alleviating the symptoms of IBD.Methodology: A narrative review was conducted using the Scopus and PubMed databases. It includes recent case reports, original studies, systematic reviews, and meta-analyses published from 1998 to 2025. All publications were analysed to explore the relationship between creatine and IBD.Results: Creatine supplementation, primarily used in sports, is not widely used among IBD patients. Studies suggest that creatine supplementation alleviates multiple IBD symptoms. A recent case report on “creatine monotherapy” shows improvement in prior ulceration and inﬂammation.Conclusions: As IBD rates increase, more research is needed to fully manage CD and UC. Creatine monohydrate supplementation shows promising results in improving gastrointestinal health. Due to the absence of randomized controlled trials and controlled clinical trials examining various dosages, further investigation is necessary to recommend it as a specific treatment.